The Moral Community Divide: Underage Marijuana Use Across Religious Contexts - Nie, Fanhao (Journal for the scientific study of religion, 2019)
Compared to individual-level research on religion and marijuana use, much less research has been conducted to investigate how the overall religious context of a geographic location may influence marijuana use during adolescence and early adulthood. Using multilevel analyses on two waves of the National Study of Youth and Religion (NSYR) merged with county-level variables from the U.S. Census and the Religious Congregations and Membership Study (RCMS), this study finds that a county's higher Catholic population share is negatively associated with underage marijuana use frequency even after controlling for a wide range of individual and county-level variables. Besides being robust, the Catholic contextual effect on marijuana use is also diffusive, influencing both Catholic and non-Catholic youth who live in the same county. This study highlights the importance of viewing religious influence on substance use as a contextual, cultural force across different kinds of religious moral communities.